2018
DOI: 10.1111/sji.12655
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous protein and enzyme fragments induce immunoglobulin E‐independent activation of mast cells via a G protein‐coupled receptor,MRGPRX2

Abstract: Mast cells play a central role in inflammatory and allergic reactions by releasing inflammatory mediators through 2 main pathways, immunoglobulin E-dependent and E-independent activation. In the latter pathway, mast cells are activated by a diverse range of basic molecules (collectively known as basic secretagogues) through Mas-related G protein-coupled receptors (MRGPRs). In addition to the known basic secretagogues, here, we discovered several endogenous protein and enzyme fragments (such as chaperonin-10 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Others and ours studies indicate that MRGPRs mediate the IgE‐independent activation of MCs by basic secretagogues such as SP, VIP, and PACAP (6‐27). Recently, we showed that several endogenous enzyme‐fragmented peptides (CNP fragments and chaperonin‐10 fragments) were MRGPRX2 ligands and could induce degranulation in MCs . McNeil et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others and ours studies indicate that MRGPRs mediate the IgE‐independent activation of MCs by basic secretagogues such as SP, VIP, and PACAP (6‐27). Recently, we showed that several endogenous enzyme‐fragmented peptides (CNP fragments and chaperonin‐10 fragments) were MRGPRX2 ligands and could induce degranulation in MCs . McNeil et al.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that several endogenous enzyme-fragmented peptides (CNP fragments and chaperonin-10 fragments) were MRG-PRX2 ligands and could induce degranulation in MCs. 23 McNeil et al…”
Section: Positive Correlation Between the Inductive Activities Of Degmentioning
confidence: 99%
“…Consequently, cell models that can quickly and accurately identify peptides with a MCD hazard early in the drug development process are highly beneficial to avoid development of peptide drugs with MCD-associated liabilities (such as anaphylactoid reactions and/or ISR). MRGPRX2 has been reported to be responsible for activation of the non-IgE peptidergic MCD pathway by a number of basic secretagogues and therapeutic drugs (McNeil et al 2015;Tatemoto et al 2018). MRGPRX2 is part of the Mas-related gene (MRG) family of GPCR that is comprised of almost 50 members divided into several subfamilies (A-H and X); the X sub-family is specific to primates, including humans, macaques, and rhesus monkeys (Solinski et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…7,[26][27][28] Thus, in contrast to the activation pattern of other GPCRs, MRGRX2 is activated by a broad range of ligands. 29,30 Unlike other GPCRs (eg, C3aR), MRGPRX2 may be resistant to phosphorylation, internalization, and desensitization following activation by certain, albeit not all, agonists. 15,31 The latter fact may explain the responsiveness of MRGPRX2 to multiple ligands.…”
Section: How Is Mrgprx2 Activated?mentioning
confidence: 99%
“…Identification of these MC-activating protein fragments provides future opportunities in study of the role of MRGPRX2 in various inflammatory disorders. 29,191 C48/80. C48/80, which is a synthetic polymer produced by condensation of N-methyl-p-methoxy phenylethylamine with formaldehyde, has been known to activate human and rodent MCs since the early 1970s.…”
Section: Drugs That Activate Mrgprx2mentioning
confidence: 99%